2010
DOI: 10.1007/s11661-010-0303-6
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Changes in Chemistry and Testing Temperature on Mechanical Behavior of Al-Based Amorphous Alloy Ribbons

Abstract: The effects of changes in composition, testing temperature, strain rate, and thermal exposure on the flow behavior of a series of Al-Gd-Ni-X amorphous alloy ribbons have been determined via hot microhardness and tension testing. It is shown that the addition of Fe, Co, and Fe/Co combination into these materials increases the strength, T g , and T x1 in addition to the activation energy for crystallization, whereas the window between T g and T x1 remains similar. The uniaxial tensile tests show these ribbons ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Therefore, the tensile strength of samples in air decreased only 61 MPa at 430 °C, while the tensile strength decreased 187 MPa at 420 °C. Huang et al [20] studied the mechanical properties of Al 87 Gd 6 Ni 7 , Al 86 Gd 6 Ni 7 Fe 1 , and Al 86 Gd 6 Ni 7 Co 1 amorphous alloys. It was found that the fracture strength of samples gradually increased to 1,050 MPa and 1,065 MPa after adding Fe and Co with higher the Moh's hardness to Al-Gd-Ni (950 MPa).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the tensile strength of samples in air decreased only 61 MPa at 430 °C, while the tensile strength decreased 187 MPa at 420 °C. Huang et al [20] studied the mechanical properties of Al 87 Gd 6 Ni 7 , Al 86 Gd 6 Ni 7 Fe 1 , and Al 86 Gd 6 Ni 7 Co 1 amorphous alloys. It was found that the fracture strength of samples gradually increased to 1,050 MPa and 1,065 MPa after adding Fe and Co with higher the Moh's hardness to Al-Gd-Ni (950 MPa).…”
Section: Discussionmentioning
confidence: 99%
“…Lewandowski summarized the deformation behavior of metallic glasses with shear strain rate and normalized testing temperature [25] . During the tensile test, the shear bands will be constantly activated, and the stress will suddenly drop down every time a shear band operates.…”
Section: Discussionmentioning
confidence: 99%
“…These results are in good agreement with the studies of hardness in partially crystallized amorphous alloys, which show that the increase in hardness can be correlated with the increase in volume fraction of crystalline phases. [16,17] These changes in microhardness can be correlated with the change in microstructure, induced by thermal treatment, through evolution of the average crystal size of the crystalline phases in the alloy ( Figure 5(b)). The average crystal size is shown to have a significant influence on the change in microhardness.…”
Section: Influence Of the Structural Transformations On Microhardnessmentioning
confidence: 99%
“…Recent studies of bulk metallic glasses and amorphous alloy ribbons showed that the increase in time of thermal treatment at the crystallization temperature increased the hardness of these partially crystallized materials, which was correlated with the increase in volume fraction of crystalline phases. [16,17] The Fe 81 Si 4 B 13 C 2 amorphous alloy was investigated to a significant degree [18][19][20][21] with respect to phase transformations and kinetics of crystallization [22,23] and the effect of these transformations on magnetic and electric properties. [24] However, the mechanical properties of this alloy and the influence of thermally induced structural transformations on these properties were not previously studied in detail.…”
Section: Introductionmentioning
confidence: 99%